Pengembangan Potensi Wisata Asam Jokowi sebagai Produk Wisata Berbasis Masyarakat Kawasan Perbatasan di Desa Tulakadi Kabupaten Belu - Nugraha, Yudha Eka (Jurnal Master Pariwisata (JUMPA), 2021)
This research is concerned with cross-border tourism in Asam Jokowi, Desa Tulakadi. It aims to determine the potential of tourism based on supporting and inhibiting factors of rural tourism development in Asam Jokowi and analyzing the strategy of Community Based Tourism in Desa Tulakadi. The research was conducted in Desa Tulakadi. This study uses qualitative method which the data obtained through depth interviews with five key informants. Futhermore, the data were analyzed using IFAS EFAS analysis and SWOT analysis. The result of this study indicate that Desa Tulakadi has a potential tourist attraction. Based from IFAS EFAS analysis, Asam Jokowi Desa Tulakadi classified in Quadrant I (Agresive Growth) which means the strategies needed to maintain and improve the quality of tourism potential attractions. The role and cooperation of the community, media, academics, and government are necessary to develop the tourism potential of Asam Jokowi in Desa Tulakadi as a tourist destination in the cross-border region. Keywords: Development Strategy, Tourism Product, Community Based Tourism, Cross-Border Tourism, Rural Tourism